Matrix Metalloproteinase 7 Expression and Apical Epithelial Defects in Atp8b1 Mutant Mouse Model of Pulmonary Fibrosis - Emma Westermann-Clark; Ramani Soundararajan; Jutaro Fukumoto; Sahebgowda Sidramagowda Patil; Timothy M. Stearns; Smita Saji; Alexander Czachor; Helena Hernandez-Cuervo; Mason Breitzig; Sudarshan Krishnamurthy; Richard F. Lockey; Narasaiah Kolliputi (Biomolecules, 2022)
Abnormalities in airway epithelia and lung parenchyma are found in Atp8b1 mutant mice, which develop pulmonary fibrosis after hyperoxic insult. Microarray and ingenuity pathway analysis (IPA) show numerous transcripts involved in ciliogenesis are downregulated in 14-month (14 M) -old Atp8b1 mouse lung compared with wild-type C57BL/6. Lung epithelium of Atp8b1 mice demonstrate apical abnormalities of ciliated and club cells in the bronchial epithelium on transmission electron microscopy (TEM). Matrix metalloproteinase 7 (MMP7) regulates of ciliogenesis and is a biomarker for idiopathic pulmonary fibrosis (IPF) in humans. Mmp7 transcript and protein expression are significantly upregulated in 14 M Atp8b1 mutant mouse lung. MMP7 expression is also increased in bronchoalveolar lavage fluid (BAL). Immunohistochemistry is localized MMP7 to bronchial epithelial cells in the Atp8b1 mutant. In conclusion, MMP7 is upregulated in the aged Atp8b1 mouse model, which displays abnormal ciliated cell and club cell morphology. This mouse model can facilitate the exploration of the role of MMP7 in epithelial integrity and ciliogenesis in IPF. The Atp8b1 mutant mouse is proposed as a model for IPF.